From Mud to Modular: A Thematic Analysis of Children and Parental perceptions on ‘Play-ability’ of Modern Public spaces in Mumbai - Chandrasekaran, Jayashree; Sharma, Nishant (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
The contemporary urban landscape faces a "silent emergency" known as the Urban Play Crisis, a complex interplay of non-supportive environments, parental anxiety, and digital dependency. While middle childhood (ages 9–12) is a critical period for socio-emotional mastery, the physical "commons" required for this growth is rapidly shrinking. Urban density and a pervasive "surveillance culture" have transformed spontaneous play into a structured, adult-led luxury. This study frames this erosion as a failure of Design Justice, where top-down planning excludes children as primary users. Exploring the lived realities of children and caregivers in Mumbai, the research identifies a gap in understanding the psychological gatekeeping within dense urban fabrics. Thematic analysis reveals that safety anxieties and inadequate amenities often override developmental needs, leading to "engagement boredom" in older children. The authors advocate for participatory design that reclaims the city as a "real-world classroom," fostering autonomy, risk-taking, and social belonging for the next generation.